BDY413: Bioinformatics / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2023)
This is an introductory course on the uses of mathematical and computational methods to extract information from biological data. It includes the use of computer as a tool for biological research. Students are required to have prior knowledge of theoretical and practical aspects of molecular biology, and computer programming or computer hardware.